The macroeconomics of abortion: A scoping review and analysis of the costs and outcomes. - Yana van der Meulen Rodgers; Ernestina Coast; Samantha R Lattof; Cheri Poss; Brittany Moore (PLoS ONE)
Background Although abortion is a common gynecological procedure around the globe, we lack synthesis of the known macroeconomic costs and outcomes of abortion care and abortion policies. This scoping review synthesizes the literature on the impact of abortion-related care and abortion policies on economic outcomes at the macroeconomic level (that is, for societies and nation states). Methods and findings Searches were conducted in eight electronic databases. We conducted the searches and application of inclusion/exclusion criteria using the PRISMA extension for Scoping Reviews. For inclusion, studies must have examined one of the following macroeconomic outcomes: costs, impacts, benefits, and/or value of abortion care or abortion policies. Quantitative and qualitative data were extracted for descriptive statistics and thematic analysis. Of the 189 data extractions with macroeconomic evidence, costs at the national level are the most frequently reported economic outcome (n = 97), followed by impacts (n = 66), and benefits/value (n = 26). Findings show that post-abortion care services can constitute a substantial portion of national expenditures on health. Public sector coverage of abortion costs is sparse, and individuals bear most of the costs. Evidence also indicates that liberalizing abortion laws can have positive spillover effects for women's educational attainment and labor supply, and that access to abortion services contributes to improvements in children's human capital. However, the political economy around abortion legislation remains complicated and controversial. Conclusions Given the highly charged political nature of abortion around the global and the preponderance of rhetoric that can cloud reality in policy dialogues, it is imperative that social science researchers build the evidence base on the macroeconomic outcomes of abortion services and regulations.